CQD-SHAP: Explainable Complex Query Answering via Shapley Values

Ein Designprinzip für Lernumgebungen zu inter-aktiven Theorembeweisern - Garnelo Abellanas, Irene (Beiträge zum Mathematikunterricht 2025)

Bridging the Reality-Virtuality Gap: Evaluating Attention Markers in a Cross-Reality Application for Improved User Coordination - Yigitbas, Enes; Kröker, Leon (Proceedings of the 17th International Conference on Ubiquitous Computing and Ambient Intelligence (UCAmI 2025))

Gamification and Physiological Feedback: A Novel Approach to Reducing Glossophobia in Virtual Reality Environments - Yigitbas, Enes; Agha, Ali Amin (Proceedings of the 17th International Conference on Ubiquitous Computing and Ambient Intelligence (UCAmI 2025))

Best Practices For Empirical Meta-Algorithmic Research: Guidelines from the COSEAL Research Network - Eimer, Theresa; Schäpermeier, Lennart; Biedenkapp, André; Tornede, Alexander; Kotthoff, Lars; Leyman, Pieter; Feurer, Matthias; Eggensperger, Katharina; Maile, Kaitlin; Tornede, Tanja; Kozak, Anna; Xue, Ke; et al.

Toward Static Analysis of Immersive Attacks - Karakaya, Kadiray; Klauke, Jonas; Yigitbas, Enes (Proceedings of the 3rd International Workshop on Virtual and Augmented Reality Software Engineering (VARSE) @ ASE 2025)

A VR End-User Development Toolbox for Media Study Students - An Initial Experience Report - Krois, Sebastian; Scharke, Kevin; Yigitbas, Enes; Oevel, Gudrun (10th International Symposium on End-User Development (IS-EUD 2025))

Fachsensible wissenschaftliche Begleitung - Sloane, Hannah Sabrina; Heidebrecht, Jana; Jenert, Tobias (Prototyp Zukunft: Lösungen für transformative Lehre im Modus des Scholarship)

Feynman-Kac formula for fiber Hamiltonians in the relativistic Nelson model in two spatial dimensions - Hinrichs, Benjamin; Matte, Oliver (Proceedings of the 2023 RIMS Workshop 'Mathematical Aspects of Quantum Fields and Related Topics')
In this proceeding we consider a translation invariant Nelson type model in two spatial dimensions modeling a scalar relativistic particle in interaction with a massive radiation field. As is well-known, the corresponding Hamiltonian can be defined with the help of an energy renormalization. First, we review a Feynman-Kac formula for the semigroup generated by this Hamiltonian proven by the authors in a recent preprint (where several matter particles and exterior potentials are treated as well). After that, we employ a few technical key relations and estimates obtained in our preprint to present an otherwise self-contained derivation of new Feynman-Kac formulas for the fiber Hamiltonians attached to fixed total momenta of the translation invariant system. We conclude by inferring an alternative derivation of the Feynman-Kac formula for the full translation invariant Hamiltonian.

On the Ising Phase Transition in the Infrared-Divergent Spin Boson Model - Betz, Volker; Hinrichs, Benjamin; Kraft, Mino Nicola; Polzer, Steffen (arXiv:2501.19362)
We prove absence of ground states in the infrared-divergent spin boson model at large coupling. Our key argument reduces the proof to verifying long range order in the dual one-dimensional continuum Ising model, i.e., to showing that the respective two point function is lower bounded by a strictly positive constant. We can then use known results from percolation theory to establish long range order at large coupling. Combined with the known existence of ground states at small coupling, our result proves that the spin boson model undergoes a phase transition with respect to the coupling strength. We also present an expansion for the vacuum overlap of the spin boson ground state in terms of the Ising $n$-point functions, which implies that the phase transition is unique, i.e., that there is a critical coupling constant below which a ground state exists and above which none can exist.

Ultraviolet Renormalization of Spin Boson Models I. Normal and 2-Nilpotent Interactions - Hinrichs, Benjamin; Lampart, Jonas; Valentín Martín, Javier (arXiv:2502.04876)
We study the ultraviolet problem for models of a finite-dimensional quantum mechanical system linearly coupled to a bosonic quantum field, such as the (many-)spin boson model or its rotating-wave approximation. If the state change of the system upon emission or absorption of a boson is either given by a normal matrix or by a 2-nilpotent one, which is the case for the previously named examples, we prove an optimal renormalization result. We complement it, by proving the norm resolvent convergence of appropriately regularized models to the renormalized one. Our method consists of a dressing transformation argument in the normal case and an appropriate interior boundary condition for the 2-nilpotent case.

Ultraviolet Renormalization of the van Hove-Miyatake Model: an Algebraic and Hamiltonian Approach - Falconi, Marco; Hinrichs, Benjamin (arXiv:2505.19977)
In this short communication we discuss the ultraviolet renormalization of the van Hove-Miyatake scalar field, generated by any distributional source. An abstract algebraic approach, based on the study of a special class of ground states of the van Hove-Miyatake dynamical map is compared with an Hamiltonian renormalization that makes use of a non-unitary dressing transformation. The two approaches are proved to yield equivalent results.

Non-Trivial Renormalization of Spin-Boson Models with Supercritical Form Factors - Falconi, Marco; Hinrichs, Benjamin; Valentín Martín, Javier (arXiv:2508.00805)
In this paper we construct the non-trivial, renormalized Hamiltonian for a class of spin-boson models with supercritical form factors, including the one describing the Weisskopf-Wigner spontaneous emission. The renormalization is performed through both a self-energy and mass renormalization, in the so-called Hamiltonian formalism of constructive quantum field theory, implemented by a non-unitary dressing transformation. This solves the problem of triviality for unitarily-renormalized supercritical spin-boson models.

Wiener-Type Theorems for the Laplace Transform. With Applications to Ground State Problems - Hinrichs, Benjamin; Polzer, Steffen (arXiv:2511.02867)
We study the behavior of a probability measure near the bottom of its support in terms of time averaged quotients of its Laplace transform. We discuss how our results are connected to both rank-one perturbation theory as well as renewal theory. We further apply our results in order to derive criteria for the existence and non-existence of ground states for a finite dimensional quantum system coupled to a bosonic field.

On the Optimal Rate of Convergence for Translation-Invariant 1D Quantum Walks - Hinrichs, Benjamin; Mittenbühler, Pascal (arXiv:2511.13409)
We study the convergence rate of translation-invariant discrete-time quantum dynamics on a one-dimensional lattice. We prove that the cumulative distributions function of the ballistically scaled position $\mathbb X(n)/{n}$ after $n$ steps converges at a rate of $n^{-1/3}$ in the Lévy metric as $n→∞$. In the special case of step-coin quantum walks with two-dimensional coin space, we recover the same convergence rate for the supremum distance and prove optimality.

Manifolds of continuous BV-functions and vector measure regularity of Banach–Lie groups - Glöckner, Helge; Schmeding, Alexander; Suri, Ali (Geometric Mechanics)

Breaking Barriers: Implementing IoT-enabled Smart Services for Competitive Advantage - Kaufmann, Jonas; Schreiner, Nick; Koldewey, Christian; Fichtler, Timm; Sommer, Franziska; Sedlmeier, Joachim; Hocken, Christian; Rabe, Martin; Kühn, Arno

product.intelligence - Datenbasiertes Produktmanagement - Grigoryan, Khoren; Lamarz, Jessica; Martin, Lucas; Asmar, Laban; Rabe, Martin; Kühn, Arno; Fichtler, Timm; Petzke, Lisa Irene; Bruchhage, Felix; Koldewey, Christian

High-magnitude headers are not associated with structural and functional brain changes in active high-level football (soccer) players - Mund, Franziska Katharina; Feddermann-Demont, Nina; Welsch, Goetz H; Schuenemann, Carsten; Fiehler, Jens; Thaler, Christian; Meyer, Lukas; Reeschke, Rebecca; Reinsberger, Claus (BMJ Open Sport & Exercise Medicine)
Objectives To date, consistent evidence for consequences of heading in football (soccer) on the structure and function of the brain is lacking, but first studies indicate a potential effect of specific high-magnitude headers. The purpose of this longitudinal, prospective study was to investigate whether potential structural and/or functional alterations within the brain were associated with (high-magnitude) heading. Methods 3T MRI sequences were obtained from active high-level male players before and after an observation period of 17.2 months (median). Cortical thickness and grey matter (GM) volume were investigated on a whole-brain level. Functional connectivity (FC) was analysed in the default mode network (DMN) and salience network (SN). During the observation period, each training and each match was videotaped and evaluated regarding the heading exposure. Significant structural and functional findings were subsequently correlated with specific header characteristics. Results 14 included participants (mean age: 20.36±3.34 years) played 5822 headers. GM volume remained unchanged, whereas cortical thickness decreased minimally from pre-measurement to post-measurement in a left precentral region (mean change: 0.048±0.128 mm; clusterwise p=0.0416). Within the SN, FC increased in one cluster (false discovery rate corrected p=0.026). FC remained stable within the DMN and between DMN and SN. Change from pre-measurement to post-measurement for the significant results did not correlate with heading variables. Conclusion Our findings may indicate no cumulative effect of heading during the observation period. As these results contrast with cross-sectional findings, more longitudinal, prospective studies with a greater sample size are urgently needed to understand potential heading effects.

Complementary Analysis of Cyclic Voltammograms and Impedance Spectra of Porous Carbon Electrodes - Reinke, Sebastian; Khamitsevich, Vera; Linnemann, Julia (2024 International Workshop on Impedance Spectroscopy (IWIS))
Porous carbons are prominent electrode materials in energy storage applications such as supercapacitors. However, rational materials development is hampered by difficulties in interpreting electrochemical impedance spectra (EIS) and drawing conclusions about promising aspects of device improvement. Here, we characterized electrodes consisting of activated carbon with polyacrylic acid binder in four different concentrations of sulfuric acid, using cyclic voltammetry and electrochemical impedance spectroscopy. Both datasets were evaluated with simple equivalent circuits and comparatively analyzed. Conductivity of the electrolyte was independently measured. Cyclic voltammograms (CV) show larger resistance and capacitance at low scan rates. Resistances obtained from EIS are in good agreement with those obtained by cyclic voltammograms particularly at high scan rates. The comparison against specific electrolyte resistance can reveal whether resistances within the solid electrode architecture or resistances within the electrolyte, partially confined by pores, are the dominant cause of increased resistance at low scan rate. Comparison between CV and EIS points to the main electrode capacitance being described by a constant phase element (CPE) used to fit the low-frequency region of EIS.
Keywords: electrochemical impedance spectroscopy; distorted cyclic voltammograms; supercapacitors; carbon